Male pheromones and their reception by females are co-adapted to affect mating success in two subspecies of brown rats. Issue 4 (23rd October 2020) - Zhang, Yao-Hua; Zhao, Lei; Fu, Shi-Hui; Wang, Zhen-Shan; Zhang, Jian-Xu
Abstract: Pheromonal communication plays a key role in the sociosexual behavior of rodents. The coadaptation between pheromones and chemosensory systems has been well illustrated in insects but poorly investigated in rodents and other mammals. We aimed to investigate whether coadaptation between male pheromones and female reception might have occurred in brown rats Rattus norvegicus . We recently reported that major urinary protein (MUP) pheromones are associated with male mating success in a brown rat subspecies, R. n. humiliatus (Rnh). Here, we discovered that MUPs were less polymorphic and occurred at much lower concentrations in males of a parapatric subspecies, R. n. caraco (Rnc), than in Rnh males, and found no association between pheromones and paternity success. Moreover, the observation of Rnc males that experienced chronic dyadic encounters and established dominance–submission relationships revealed that the dominant males achieved greater mating success than the subordinate males, but their MUP levels did not differ by social status. These findings suggest that male mating success in Rnc rats is related to social rank rather than to pheromone levels and that low concentration of MUPs might not be a reliable signal for mate choice in Rnc rats, which is different from the findings obtained in Rnh rats. In addition, compared with Rnh females, Rnc females exhibited reduced expression of pheromone receptor genes, and a lower number of vomeronasal receptor neurons were activated by MUP pheromones, which imply that the female chemosensory reception of pheromones might be structurally and functionally coadapted with male pheromone signals in brown rats.